MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA ANAK MELALUI BERMAIN MEDIA PLASTISIN PADA KELOMPOK A - Nurkhasyanah, Alfiyanti; Herlindah, Herlindah (Jurnal Anak Bangsa, 2024)
This study aims to determine the increase in children's fine motor skills through playing with plasticine media in group A RA Biharul Ulum Ma'arif Ujung Labuang. The problem in this research is how to improve children's fine motor skills through playing with plasticine media. This type of research is classroom action research (PTK) which includes two cycles. Each cycle is carried out in 3 meetings and each cycle is carried out sequentially consisting of 4 stages, namely ( 1).Planning, (2).Implementing actions, (3).Observation, (4).Reflection. The research subjects were 21 children consisting of 9 boys and 12 girls. Data collection techniques used observation and documentation. The data analysis technique used was qualitative, the increase in learning outcomes that occurred in cycle 1, which was held three times, resulted in Very Good Development Criteria (BSB) with a percentage of 0.19%. In cycle 2 there was an increase in fine motor skills through playing with plasticine in group A, there was an increase in the criteria for Very Well Developed (BSB) with a percentage of 1.76%. Using plasticine media can improve children's fine motor skills, therefore it is important for teachers to give examples to children and provide motivation to children, one of which is by giving children the opportunity to create free forms of plasticine play activities that can be shaped and processed according to their wishes and needs. child's imagination